Ceramic production and distribution in protopalatial Crete : technological, economic and social perspectives. - Knappett, Carl James (Apollo - University of Cambridge Repository, 1997)
Excavations twenty five years ago at the sites of Quartier Mu (Mallia), and Myrtos Pyrgos revealed extensive pottery deposits datable to the Middle Minoan IIB phase of the Protopalatial period. The fine ceramics of the village site of Myrtos Pyrgos are very similar to those at the palatial site of Mallia. Other sites in East Crete, such as Gournia and Vasiliki, also share the same fine pottery styles. These patterns of ceramic stylistic regionalism have been interpreted by various scholars as evidence for an early state centred on the palatial site of Mallia. Yet basing such political interpretations almost exclusively on ceramic stylistic regionalism is a problematic process; ethnoarchaeological work suggests that cultural units thus reconstructed need not tally with units of economic or political activity. As such they do not tell us a great deal about the dynamic economic workings of an early state. Using pottery as a source of information on such economic processes (production and distribution) requires a fresh analytical perspective. As technology is here differently perceived than in most Minoan ceramic studies, I consider it an impo1tant part of this thesis to build up a detailed picture of the nature of technology, and how one might go about understanding past technological choices and activities when faced with the finished products alone. The traditional use of typological and stylistic data is in itself inadequate, and has to be supplemented by, and integrated with, technological and compositional data. In terms of methodology this involves detailed analyses of vessel size and shape, fabric (using thin section petrography), construction technique, surface treatment and decoration. Technical variants in different stages of production are thereby identified. Moreover, assessments are made of the skill, standardisation and labour input in the execution of these production steps. Before -the main data from Mallia and My1tos Pyrgos are presented, various Middle Minoan ceramic deposits from Knossos are considered, in an attempt to place the technical choices to be observed at Mallia and Pyrgos into an historical context. I focus patticularly on the development of the wheelthrowing technique from the time of its introduction in Middle Minoan IB. Material from Knossos is chosen because it is one of the few sites with a good sequence of closed deposits from the Middle Minoan 1B and IIA phases. Ultimately the pottery from Mallia and Pyrgos is presented according to the methodology outlined above; a particular combination of standardisation, skill and labour input is labelled a 'technological profile ' . The various patterns of production activity thus reconstructed are interpreted in terms of modes of production, such as administered, centralised and noncentralised. The presence of these different so,ts of production arrangement at the two sites then allows us to make some limited observations as to the nature of economic organisation across the region. On this basis we may then assess critically whether the term 'early state ' is appropriate, and consider in more detail alternative types of state organisation.
This thesis is not available on this repository until the author agrees to make it public. If you are the author of this thesis and would like to make your work openly available, please contact us: thesis@repository.cam.ac.uk.
Cambridge University Library can make a copy of this work available only for the purposes of private study and non-commercial research. Copies should not be shared or saved in any shared facilities. Copyright over the content of these works is with their authors. Theses from the Library collection are considered unpublished works and according to UK legislation quoting from them is not allowed without permission from their author. If you can commit to these terms, please complete the request form which you can find through this link: https://imagingservices.lib.cam.ac.uk/
Please note that print copies of theses may be available for consultation in the Cambridge University Library's Manuscript reading room. Admission details are at http://www.lib.cam.ac.uk/collections/departments/manuscripts-university-archives